Taxonomic changes in the genus Diabrotica Chevrolat (Coleoptera: Chrysomelidae: Galerucinae): results of a synopsis of North and Central America Diabrotica species - Derunkov, A.; Konstantinov, A. (Zootaxa, 2013)
The following new synonyms in Diabrotica Chevrolat 1836 are proposed: D. flaviventris Jacoby 1887 and D. tibialis Ja-coby 1887 are synonyms of D. adelpha Harold 1875; D. peckii Bowditch 1911 is a synonym of D. bioculata Bowditch 1911; D. nummularis Harold 1877 is a synonym of D. circulata Harold 1875; D. linensis Bechyné 1956 is a synonym of D. trifurcata Jacoby 1887; D. brunneosignata Jacoby 1887 is a synonym of D. sinuata Olivier 1790; D. duplicata Jacoby 1887 is a synonym of D. viridifasciata Jacoby 1887. Diabrotica cyaneomaculata Jacoby 1887 does not share the synapo-morphies of Diabrotica and is treated as incertae sedis. Diabrotica tripunctata (Fabricius) is removed from synonymy with D. sinuata Olivier and is considered to be a valid species. The original combination is restored for Diabrotica fasciata Kirsch, the species being transferred from Paranapiacaba Bechyné back to Diabrotica. It was found that the type series of D. godmani Jacoby contains seven different taxa: one is D. godmani itself; one is D. championi Jacoby; one is D. quad-ricollis Jacoby; three are unidentified Diabrotica species, each different from the others; and one is not a Diabrotica. The type series of D. viridicollis Jacoby contains four different taxa, D. viridicollis Jacoby itself and three different unidenti-fied Diabrotica species.